Determining the Priority of Business Development Strategy for Kunir Jalak Business Unit, SMK Muhammadiyah 1 Moyudan, Sleman - Siti Mahsanah Budijati; Fatma Hermining Astuti; Wandhansari Sekar Jatiningrum; Aziz Ichwanudin (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: Kunir Jalak business unit is part of UPJ Surya Boga belonging to the Catering Department at SMK Muhammadiyah 1 Moyudan, Sleman. This unit produces a powder drink made from turmeric, ginger, and temulawak. This drink is intended to maintain immunity, considering the covid 19 pandemic. The Kunir Jalak business unit is relatively new, so it still needs assistance to develop its business. This community service activity aims to assist in determining business development strategies so that the Kunir Jalak business unit can be more developed. Contribution: The impact of community service activities is shown by increasing partners’ empowerment in identifying strengths, weaknesses, opportunities, and threats (SWOT) for the Kunir Jalak business unit and determining the alternative business development strategy, which has never been done before. Method: The method used is Focus Group Discussion (FGD) to determine strengths, weaknesses, opportunities, and threats (SWOT) and determine business development strategies. Furthermore, the Analytical Hierarchy Process (AHP) approach determines strategic priorities. Results: AHP analysis shows three business development strategies with the highest priority, namely: Weakness-Treats-1 (WT-1), Strength-Treats-1 (ST-1), and Weakness-Opportunity-2 (WO-2). Conclusion: Following the objectives of the community service program, it means that the priority of business development strategies can be determined, which can be used as guidelines for developing the business unit of Kunir Jalak.